Pengaruh Variasi Elektrolit (NaCl dan N2SO4) Untuk Meningkatkan Kinerja Komposit 5%Cu-TiO2/BiVO4 Dalam Fotoelektrokimia Water Splitting - Nurhayati, Siti; Vera Pangni Vahriani; Sarah Dampang; Muhammad Fahmi Hakim; Bunga Nurkhalifah (Jurnal Serambi Engineering, 2025)
The demand for environmentally friendly energy sources has encouraged the use of photoelectrochemical (PEC) technology to produce hydrogen from water. This study aims to evaluate the performance of a 5% Cu–TiO₂/BiVO₄ composite material. The main focus is to examine the effect of two types of neutral electrolytes, NaCl and Na₂SO₄, on the performance of a single-compartment PEC system. Based on characterization results using SEM-EDS and UV-Vis DRS, copper (Cu) doping successfully reduced the material's band gap to 2.02 eV and improved charge separation efficiency. System testing showed that the NaCl solution produced the highest initial voltage of 0.73 V and exhibited relatively stable performance, although it posed a potential risk of electrode corrosion. In contrast, Na₂SO₄ produced a lower voltage (0.66 V) but was more chemically stable and safer for long-term use. The results indicate that combining Cu–TiO₂/BiVO₄ material with appropriate electrolyte selection can be an effective strategy to improve the efficiency of PEC systems for hydrogen generation from light.